1986
DOI: 10.2355/isijinternational1966.26.807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Microstructure and Chemical Compositions of Steels on Formation of Fe-Zn Compounds during Continuous Galvanizing

Abstract: Synopsis The effects of surface microstructure and chemical compositions on characteristics of Fe-Zn compounds which formed on continuously galvanized steel sheets have been investigated by using ultra low carbon and low carbon steels. From SEM observation, morphology of Fe-Zn compounds formed at interface between steel and plating layer were classified into three types; outburst structure, fine granular structure, and pillar-like structure. The amount of outburst structure increases with decreasing solute car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…This observation suggests that the formation of at the coating-steel interface differs from grain boundThe Al content in the coating overlay is lowest at 0.15 pct melt Al level on both the IF and the LC steels. As ary nucleation of outbursts reported by Nishimoto et al [4] Fig. 10-Composition maps for a cross section of IF steel hot dipped in 0.18 pct Al zinc melt.…”
Section: Stem Microanalysis Of Coatings For Al and Fe Distributionsmentioning
confidence: 94%
See 1 more Smart Citation
“…This observation suggests that the formation of at the coating-steel interface differs from grain boundThe Al content in the coating overlay is lowest at 0.15 pct melt Al level on both the IF and the LC steels. As ary nucleation of outbursts reported by Nishimoto et al [4] Fig. 10-Composition maps for a cross section of IF steel hot dipped in 0.18 pct Al zinc melt.…”
Section: Stem Microanalysis Of Coatings For Al and Fe Distributionsmentioning
confidence: 94%
“…While Hertveldt et al [9] zinc during continuous galvanizing has been investigated by determined that the inhibition layer is composed of a zinca number of researchers. Nishimoto et al [4] concluded that bearing FeAl or FeAl 2 compound, Guttmann, et al [10] indicarbon and phosphorous in solution in steel inhibited the cated that the inhibition layer is comprised of Fe 2 Al 5 with formation of zinc-iron alloy outbursts in the coating. Saito a high zinc content.…”
Section: Introductionmentioning
confidence: 99%
“…Better knowledge of the phase make-up of the coatings and of its effect on formability is therefore required to optimize these coatings. The nature and the distribution of the intermetallics depend mainly on the steel substrate chemistry and different parameters of the galvannealing process (bath and annealing temperatures, annealing time, A1 bath content, etc., Fader1 et al, 1992;L'Ecuyer et al, 1992;Nishimoto et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…2,4) Inagaki et al 2) observed a thick Fe2Al5Znx layer in the coatings produced with a 0.15 wt% bath aluminum as compared with the coatings produced with a 0.13 wt% bath aluminum. This intermetallic layer acts as a barrier for FeZn diffusion and inhibits the formation of ζ-phase and δ-phase.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown by multiple researchers that these alloying elements affect the steel/zinc interaction. Inagaki et al, 2) Nishimoto et al, 4) Lin et al 5) showed that phosphorus and carbon can segregate to the surface and grain boundaries and inhibit the outburst reaction and slows down the formation of Fe-Zn intermetallic compounds. Rangarajan et al 6) found carbon and phosphorus segregation in extra low carbon steels and rephosphorized steels, respectively.…”
Section: Introductionmentioning
confidence: 99%